A Bibliometric Review of Renewable Energy Financing and Sustainable Development - Judijanto, Loso; Nampira, Ardi Azhar; Auliani, Restu; Sinaga, Jernita (Westscience Press, 2025)
This study presents a comprehensive bibliometric review of the scholarly literature on renewable energy financing and its link to sustainable development. Utilizing data from the Scopus database and analyzed through VOSviewer, the study maps thematic clusters, keyword co-occurrences, author collaborations, and country-level partnerships from 2000 to 2024. The findings reveal that